Synthesis of 1, 3, 4, 6‐Tetra‐O‐acetyl‐l‐gulose. Issue 2 (20th December 2016) - Che, Rui; Liu, Xingui; Lu, Wei
Abstract: A novel, practical and concise synthesis of 1, 3, 4, 6‐tetra‐ O ‐acetyl‐ l‐ gulose is described, using d ‐glucuronolactone as the starting material and other inexpensive and readily available agents (22% overall yield in 9 steps). With this method, the synthesis of l‐ gulose and the tumor‐targeting disaccharide of BLMs can be more efficient and convenient. Abstract : A novel, practical and concise synthesis of 1, 3, 4, 6‐tetra‐ O ‐acetyl‐ l ‐gulose was described, using easily available and non‐toxic reagents.